Quantifying epileptogenesis in rats with spontaneous and responsive brain state dynamics. Issue 1 (22nd April 2020) - Crisp, Dakota N; Cheung, Warwick; Gliske, Stephen V; Lai, Alan; Freestone, Dean R; Grayden, David B; Cook, Mark J; Stacey, William C
Abstract: There is a crucial need to identify biomarkers of epileptogenesis that will help predict later development of seizures. This work identifies two novel electrophysiological biomarkers that quantify epilepsy progression in a rat model of epileptogenesis. The long-term tetanus toxin rat model was used to show the development and remission of epilepsy over several weeks. We measured the response to periodic electrical stimulation and features of spontaneous seizure dynamics over several weeks. Both biomarkers showed dramatic changes during epileptogenesis. Electrically induced responses began to change several days before seizures began and continued to change until seizures resolved. These changes were consistent across animals and allowed development of an algorithm that could differentiate which animals would later develop epilepsy. Once seizures began, there was a progression of seizure dynamics that closely follows recent theoretical predictions, suggesting that the underlying brain state was changing over time. This research demonstrates that induced electrical responses and seizure onset dynamics are useful biomarkers to quantify dynamical changes in epileptogenesis. These tools hold promise for robust quantification of the underlying epileptogenicity and prediction of later development of seizures. Abstract : This work identified two novel electrophysiological biomarkers that quantify epilepsy progression in the tetanus toxin rat model: the response to periodic electrical stimulation and features of spontaneous seizure dynamics. Both biomarkers quantify the evolution of epileptogenesis over weeks. Graphical Abstract: